Cross Carpeting and the Challenges to Democratic Culture and Political Stability in Nigeria's Fourth Republic - Okolie, Ugo Chuks (The Indonesian Journal of International Clinical Legal Education, 2021)
Cross carpeting is an act of swapping political parties. It is an act of changing party allegiance or moving from one party to another. Cross carpeting in known by different nomenclature such as party hopping, party switching, party crossover, party defection, party decamping, floor crossing, canoe-jumping, political party prostitution and political nomadism. The spate of cross carpeting at all the levels of government in Nigeria is beginning to cause serious political tension, hostility and a source of worry to Nigerians. It is against this backdrop that this study seeks to examine the effect of cross carpeting on democratic culture and political stability in Nigeria’s fourth republic. Cross - sectional research method was adopted and data was collected via a survey of 300 respondents in south – south geopolitical zone of Nigeria. Data collected were analyzed using correlation and linear regression analysis with the aid of Statistical Package for Social Science (SPSS) version 23. The findings of the study revealed that cross carpeting negatively and significantly impacts on democratic culture and political stability in Nigeria’s fourth republic. On the basis of these findings, the study recommends among others that every political party should have ideologies, programme and policies which will serve as a compass to their members and discourage them from defecting to another party.